Fresno County Bar Association Luncheon with Justice Cruz Reynoso - Watkins, Howard::::::::: (1982)
ALJ Rolf Gadebusch by doorway, Marvin Baxter, Lenore Schreiber, Justice Reynoso, Doug Jensen, Thomas Tusan